Ar Lietuvos Didžioji Kunigaikštystė buvo federacija? - Norkus, Zenonas (Lietuvos istorijos studijos, 2024)
According to received wisdom in the historiography of the Grand Duchy of Lithuania (GDL), going back to M. Dovnar-Zapolski, M. Liubavski, O. Halecki, the territorial form of government in the GDL was federal in the late XV-early XVI century. The paper critically reviews the arguments advanced in favor of this thesis and argues that the concept of empire describes the territorial organization of GDL in a more accurate way. The criticism of the federalist theory is grounded in the conceptual analysis of the state forms provided by the distinguished Lithuanian historian and law theorist Mykolas Rėimeris (1880-1945). In his analysis, M. Rėimeris draws the distinction between a unitary state and three types of state compounds: federation, confederation, and empire. While federation and empire share the principle of subordination as the mode of organization, in the empire this is the subordination to a privileged metropole territory and cultural-ethnic group, while in federation all territories are subordinated to the federal center on parity grounds, all participating in federal government. Supplementing M. Rėimeris’ ideas with those from the contemporary comparative sociological research on empires and imperialism (S. Eisenstadt, M. Doyle, A. Motyl, Ch. Tilly), the author argues that GDL was an empire because relations between Lithuania in the strict sense (including also some Russian lands annexed by the early XV century) and Polotsk, Vitebsk, Smolensk, Volynia, Kiev, Samogitia, etc. were those of subordination of the periphery to the imperial metropole. The proponents of the federalist thesis mistake as federalism what in reality was a system of indirect rule characteristic for premodern empires. The historiographical tradition was blind to imperial features of GDL because it implicitly or explicitly compared GDL with the Moscow state, considering it as a paradigmatic case of empires. However, the Moscow empire represents only one specific type of empire - Westphalian empire, distinguished by the early application of direct rule. While most medieval polities were transformed into sovereign territorial states and Westphalian empires in the early modern time, GDL was unique in following the path of federalization. However, GDL was transformed into a federation only on the eve of the Lublin Union in 1569, while in the XIV-first half of the XVI century it was a traditional empire, including metropolitan military agrarian domains and indirectly ruled peripheral areas shading into areas of mere hegemony.